Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1365-3083.2006.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunoserological Characteristics of Mixed Connective Tissue Disease Associated with Pulmonary Arterial Hypertension

Abstract: We investigated the clinical characteristics and immunoserological alterations in patients with mixed connective tissue disease (MCTD) associated with pulmonary arterial hypertension (PAH). Anti-U1RNP autoantibodies, anti-endothelial cell antibodies (AECA) and serum thrombomodulin (TM) as well as von Willebrand factor antigen (vWFAg) concentrations were measured in 25 patients with MCTD associated with PAH and in 154 MCTD patients without PAH. The results showed that the probability of survival was lower in MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 28 publications
0
25
1
2
Order By: Relevance
“…A type of PAH occurs secondarily to collagen vascular disorders, such as systemic sclerosis and mixed connective tissue disease (MCTD). Interestingly, PAH with MCTD presents with a prominent characteristic of endothelial degeneration and proliferation, probably due to the pathogenic contribution of autoantibodies to endothelial cells [28,29]. This characteristic may be a pathological consequence of immune-mediated mechanisms shared with the present model.…”
Section: Discussionmentioning
confidence: 92%
“…A type of PAH occurs secondarily to collagen vascular disorders, such as systemic sclerosis and mixed connective tissue disease (MCTD). Interestingly, PAH with MCTD presents with a prominent characteristic of endothelial degeneration and proliferation, probably due to the pathogenic contribution of autoantibodies to endothelial cells [28,29]. This characteristic may be a pathological consequence of immune-mediated mechanisms shared with the present model.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies from Miyata, et al 4,10 and Vegh, et al 11 showed a higher prevalence of aCL antibodies in patients with MCTD and PAH, but they did not investigate anti-β 2 -GPI levels.…”
Section: Discussionmentioning
confidence: 94%
“…vWFAg is a circulating glycoprotein, synthesized by endothelial cells - and an increased serum concentration of vWFAg has been shown to be a marker of endothelial dysfunction in scleroderma, SLE and MCTD patients with PAH [10,44]. …”
Section: Discussionmentioning
confidence: 99%
“…The lung is the most frequent predilection place of the vascular damage, however, and may eventually lead to pulmonary arterial hypertension (PAH) [8]. Our group and others found that PAH might be associated with coexistent antiphospholipid and anti-endothelial cell antibodies (AECAs) [9,10]. In our previous study we found that AECA provokes the surface expression of E-selectin and the activation of endothelial cells [11].…”
Section: Introductionmentioning
confidence: 99%